VIRTUAL REALITY INTERVENTIONS FOR WAR-RELATED PSYCHIATRIC DISORDERS: A REVIEW OF EXPOSURE, NON-EXPOSURE, AND MULTIMODAL APPROACHES - Jasak, Paulina; Majewski, Michał; Żółtowska, Marta; Wesołowska, Aleksandra (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Armed conflict results in severe psychiatric disorders such as post-traumatic stress disorder (PTSD), depression, and anxiety, often associated with repeated trauma exposure. According to DSM-5 criteria, PTSD involves clusters of symptoms including intrusion, avoidance, and negative alterations in cognition and mood. As military populations frequently display resistance to standard evidence-based treatments like cognitive-behavioural therapy (CBT), alternative interventions are required.Purpose: This review examines virtual reality (VR)-based therapies, categorising them into non-exposure (e.g., relaxation, biofeedback), exposure-based (VRET), and multimodal approaches, specifically Multi-modal Motion-assisted Memory Desensitisation and Reconsolidation (3MDR).Methodology: A comprehensive search of PubMed was conducted to identify studies examining VR interventions for war-related psychiatric disorders, with a specific focus on more recent literature published up to 2025. Additional studies were identified through manual screening of relevant systematic reviews. The search incorporated keywords related to PTSD, military personnel, virtual reality and exposure therapy. We included randomized controlled trials, case reports, and meta-analyses, while articles not published in English were excluded.Results: VR-based interventions demonstrate promising efficacy in reducing symptoms of war-related psychiatric disorders, particularly in treatment-resistant military populations, and when used as an adjunct to conventional therapies such as CBT. However, current evidence remains limited and heterogeneous, highlighting the need for more rigorous randomized controlled trials to establish long-term effectiveness, safety, and standardised clinical protocols.Conclusions: VR offers immersive, controlled environments that may enhance emotional engagement and reduce dropout rates. While promising as an adjunctive or alternative tool for treatment-resistant cases, VR implementation requires careful clinical assessment and consideration of individual patient needs.